2008
DOI: 10.1016/j.jpainsymman.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Methylnaltrexone for the Treatment of Opioid-Induced Constipation in Patients with Advanced Illness: A Double-Blind, Randomized, Parallel Group, Dose-Ranging Study

Abstract: Methylnaltrexone, a peripherally-acting quaternary opioid antagonist, is an investigational treatment for opioid-induced constipation in patients with advanced illness. This randomized, parallel-group, repeated dose, dose-ranging trial included a double-blind phase for one week followed by an open-label phase for a maximum of three weeks. Opioid-treated patients with advanced illness who met criteria for opioid-induced constipation despite laxative therapy were potentially eligible. Double-blind treatment occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
1
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(145 citation statements)
references
References 14 publications
2
134
1
8
Order By: Relevance
“…Opinions of respected authorities/Consensus panels Thomas et al [17] To evaluate the safety and efficacy of methyl naltrexone 0.15 mg/kg subcutaneously every other day for two weeks.…”
Section: Level VImentioning
confidence: 99%
See 1 more Smart Citation
“…Opinions of respected authorities/Consensus panels Thomas et al [17] To evaluate the safety and efficacy of methyl naltrexone 0.15 mg/kg subcutaneously every other day for two weeks.…”
Section: Level VImentioning
confidence: 99%
“…The impact of constipation on patients' quality of life is important, especially for cancer patients [17]. Whose quality of life is already significantly impaired by the illness itself, constipation has been deemed by cancer patients to be an even greater source of discomfort than the pain they suffered.…”
Section: Introductionmentioning
confidence: 99%
“…senna plus docusate), although a recent study has demonstrated the efficacy of senna alone (35). Once constipation occurs, stimulant or osmotic laxatives should be early administered: when response to common laxatives is unsatisfactory and constipation is clearly related to opioid treatment, methylnaltrexone, an opioid antagonist that works on the receptors of the gastrointestinal tract, can be subcutaneously administered as a rescue therapy (36,37). Although many drugs administered in cancer patients can be responsible of sedation, this symptom is generally attributed to opioid therapy.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L I -Opioid-mentioning
confidence: 99%
“…Different controlled studies have shown that methylnaltrexone promptly and predictably induced laxation in cancer patients with opioid-induced constipation. Bowel movements were observed in about half of patients within 4 h of administration, independent of age and opioid doses [30,36].…”
Section: New Opioid Formulationsmentioning
confidence: 99%